Apropriação social da ciência e da tecnologia: uma leitura pelo viés do consumo - Santos, Juliana Cristina Santicioli dos (2014)
This essay presents the results of an investigation about the image consumers have regarding Science and Technology in the city of Sao Carlos. Through the technique of focal groups, there was a search for identification and discussion of the appropriate image of C&T in the consumption context, as well as the distinction if the purchase processes are determined or determining of such image and through which channels, this same perceived image, happens. The research was carried out with five groups of different social categories: university students, private school teachers, industry workers, outsourced workers and housewives. The data were examined based on the qualitative analysis of the content, specifically the synthesis of the content analysis, as to obtain, through the generalizations capable of synthetizing the collected data, likely to conclusion. From the research of consumption bias, the definition of groups called to it was accomplished based on a criterion converging to the identification of the extracts which were economically more representative to the city. The results point that the consumption, at the same time it reinforces the inherited view of C&T, as a paradox, it adds eloquent critiques to it, converging to the assumptions CTS, in special to the people led to the democratization of C&T through the Social Appropriation and Technology Science, ASC&T.